Comparative Immunomodulatory Activity of Nigella sativa L. Preparations on Proinflammatory Mediators: A Focus on Asthma - Koshak, Abdulrahman E.; Yousif, Nizar M.; Fiebich, Bernd L.; Koshak, Emad A.; Heinrich, Michael (Frontiers in Pharmacology, 2018)
Introduction A range of traditional and commercial preparations of Nigella sativa L. (NS) are frequently used in the treatment of several inflammatory diseases. Often, these preparations have poor preclinical characterisation that may lead to variable pharmacological effects. Objective To assess the in vitro effects of different chemically-defined preparations of NS on some asthma-related mediators of inflammation. Methods Different NS preparations were obtained by either seed extraction with a spectrum of solvents ranging from lipophilic to hydrophilic or commercial products. Chemically were characterised for thymoquinone by High-Performance-Liquid-Chromatography (HPLC). Immunomodulatory activity was assessed by the release of mediators (IL-2, IL-6, PGE2) in primary human T-lymphocytes, monocytes and A549 human lung epithelial cells. Results Ten distinct NS preparations showed variability in thymoquinone concentration being highest in the oily preparations extract-7 (2.7% w/w), followed by extract-10 (0.7%w/w). Similarly, the release of mediators was varied being greatest in extract-7 and 10 via significantly (<0.05) suppressing IL-2, IL-6 and PGE2 in T-lymphocytes as well as IL-6 and PGE2 in monocytes. Also, PGE2 release in A549 cells was significantly enhanced by both extracts. Conclusion The thymoquinone concentration and in vitro activity were variable among the different NS preparations. Thymoquinone-rich oily NS preparations produced potent favourable immunomodulation in asthma inflammation and can be used in future studies.